2001
DOI: 10.1016/s0014-5793(01)03002-2
|View full text |Cite
|
Sign up to set email alerts
|

Functional identification of sterol‐4α‐methyl oxidase cDNAs from Arabidopsis thaliana by complementation of a yeast erg25 mutant lacking sterol‐4α‐methyl oxidation1

Abstract: Specific primers derived from both genomic sequence data and EST cDNA sequences were used to polymerase chain reaction amplify two full-length cDNA sequences (AtSMO1 and AtSMO2), 801 and 783 bp, respectively, from an Arabidopsis thaliana cDNA library. The predicted proteins show 32 and 29% identity to the ERG25 gene from Saccharomyces cerevisiae which encodes the sterol-4K K-methyl oxidase (SMO), a membrane-bound non-heme di-iron oxygenase involved in lipid metabolism. Heterologous expression of AtSMO1 and AtS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…In any case, modification of the sterol composition observed in smo2-1/+ smo2-2 and smo2-1 smo2-2/+ mutants is probably responsible for the observed phenotype, because the proper membrane sterol composition has already been shown to be essential for correct PIN auxin efflux facilitator positioning and auxin-dependent developmental processes (Souter et al, 2002;Willemsen et al, 2003;Men et al, 2008;Pullen et al, 2010). SMO2-1 and SMO2-2 share 91% amino acid sequence identity, and both can rescue the yeast erg25 mutant (Darnet et al, 2001;Darnet and Rahier, 2004), suggesting that they exert similar functions in yeast. Consistently, we observed no obvious phenotype in single homozygous smo2-1 or smo2-2 mutants, but the smo2-1 smo2-2 double mutant was embryonic lethal, indicating that SMO2-1 and SMO2-2 share essential but redundant functions in Arabidopsis.…”
Section: Smo2-1/+ Smo2-2 and Smo2-1 Smo2-2/+ Mutants Accumulate The 4mentioning
confidence: 99%
See 3 more Smart Citations
“…In any case, modification of the sterol composition observed in smo2-1/+ smo2-2 and smo2-1 smo2-2/+ mutants is probably responsible for the observed phenotype, because the proper membrane sterol composition has already been shown to be essential for correct PIN auxin efflux facilitator positioning and auxin-dependent developmental processes (Souter et al, 2002;Willemsen et al, 2003;Men et al, 2008;Pullen et al, 2010). SMO2-1 and SMO2-2 share 91% amino acid sequence identity, and both can rescue the yeast erg25 mutant (Darnet et al, 2001;Darnet and Rahier, 2004), suggesting that they exert similar functions in yeast. Consistently, we observed no obvious phenotype in single homozygous smo2-1 or smo2-2 mutants, but the smo2-1 smo2-2 double mutant was embryonic lethal, indicating that SMO2-1 and SMO2-2 share essential but redundant functions in Arabidopsis.…”
Section: Smo2-1/+ Smo2-2 and Smo2-1 Smo2-2/+ Mutants Accumulate The 4mentioning
confidence: 99%
“…Although previous studies clearly revealed that SMO2s function biochemically as 4a-methyl-Δ 7 -sterol4a-methyl oxidases (Darnet et al, 2001;Darnet and Rahier, 2004), the physiological functions of SMO2s remain elusive. Silencing of SMO2s in Nicotiana benthamiana using the VIGS approach profoundly altered the sterol profiles of the infected plants but caused no phenotype (Darnet and Rahier, 2004).…”
Section: Smo2s Are Essential For Embryogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…2). The enzymatic characterization of these complex systems is actually under investigation (Pascal et al 1994;Darnet et al 2001). Opening of the cyclopropane ring of cycloeucalenol by COI has been thoroughly studied (Rahier et al 1989); it is a major target for morpholine fungicides, which trigger accumulation of β,19-cyclopropylsterols (Benveniste and Rahier 1992).…”
Section: Sterol Biosynthesis From Ipp To Sterol End Productsmentioning
confidence: 99%